Foundations of Analysis and Intervention with the Roma Minority in Social Services - Arenas Martínez, Miguel (Cuadernos de Trabajo Social, 2012)
Cuts in social intervention are never recommended and even less so in basic social services whose duties, claims and benefits received greatly concern the most socially disadvantaged individuals and groups. From the assumption of a constitutive dependence between comprehensive analysis and expert action as a way to incorporate knowledge, I develop a view focused on the excluded Roma minority assuming that, being one of the habitual groups, it will tell us much about usual basic social services, of the possibility of inclusive work and of the forms of intervention needed. Starting from equality and establishing the necessary relationships, I seek to provide the basis for an expert action project bringing us closer to some inescapable social dimensions, such as education, employment and housing.